Non-vitamin K oral anticoagulant treatment in elderly patients with atrial fibrillation and coronary heart disease. (1st November 2016) - Humbert, Xavier; Roule, Vincent; Chequel, Mathieu; Fedrizzi, Sophie; Brionne, Marie; Lelong-Boulouard, Véronique; Milliez, Paul; Alexandre, Joachim
Abstract: Atrial fibrillation (AF) is the most frequent sustained arrhythmia. Overall prevalence is estimated to 5.5% and the incidence increases with age. As the population ages, the prevalence and costs of AF are expected to increase. AF is the most important cause of stroke in patients > 75 years. Until recently, Vitamin K antagonists (VKAs) were the only available oral anticoagulants (OACs) evaluated for long-term treatment of patients with AF with or without coronary heart disease (CHD). This situation was challenged by introduction of non-VKA oral anticoagulants (NOACs). In AF, use of NOACs seems to be as effective and safe as VKAs, especially in elderly patients. AF and CHD are frequently associated and the question of antithrombotic management in aging patients is delicate. In elderly patients experiencing a new AF episode after an acute coronary syndrome, triple antithrombotic therapy should be as short as possible in order to decrease the risk of major bleedings. To date, there is no specific study or available guidelines regarding the NOACs use specifically in elderly patients experiencing both AF and CHD. In this review, we try to provide a perspective on NOACs future incorporation into clinical practice in elderly patients with both AF and CHD. Highlights: Atrial Fibrillation (AF) is the most important cause of stroke in patients > 75 years, Non-vitamin K oral anticoagulants (NOACs) emerged as an alternative to vitamin K oral anticoagulants (VKA) in AF context, AF is frequently associated with coronary heart disease (CHD) in elderly people, To date, there is no available guideline or trial regarding NOACs use in elderly patients experiencing both AF and CHD, This review try to provide perspectives on NOACs use in daily clinical practice in elderly patients with both AF and CHD.